Automatic Counterfeit Currency Detection Using a Novel Snapshot Hyperspectral Imaging Algorithm - Mukundan, Arvind; Tsao, Yu-Ming; Cheng, Wen-Min; Lin, Fen-Chi; Wang, Hsiang-Chen (Sensors (Basel, Switzerland), 2023)
In this study, a snapshot-based hyperspectral imaging (HSI) algorithm that converts RGB images to HSI images is designed using the Raspberry Pi environment. A Windows-based Python application is also developed to control the Raspberry Pi camera and processor. The mean gray values (MGVs) of two distinct regions of interest (ROIs) are selected from three samples of 100 NTD Taiwanese currency notes and compared with three samples of counterfeit 100 NTD notes. Results suggest that the currency notes can be easily differentiated on the basis of MGV values within shorter wavelengths, between 400 nm and 500 nm. However, the MGV values are similar in longer wavelengths. Moreover, if an ROI has a security feature, then the classification method is considerably more efficient. The key features of the module include portability, lower cost, a lack of moving parts, and no processing of images required.